RETRACTED: A 12,800-year-old layer with cometary dust, microspherules, and platinum anomaly recorded in multiple cores from Baffin Bay - Christopher R. Moore; Vladimir A. Tselmovich; Malcolm A. LeCompte; Allen West; Stephen J. Culver; David J. Mallinson; Mohammed Baalousha; James P. Kennett; William M. Napier; Michael Bizimis; Victor Adedeji; Seth R. Sutton; et al. (PLoS ONE, 2025)
The Younger Dryas Impact Hypothesis (YDIH) posits that ~12,800 years ago Earth encountered the debris stream of a disintegrating comet, triggering hemisphere-wide airbursts, atmospheric dust loading, and the deposition of a distinctive suite of extraterrestrial (ET) impact proxies at the Younger Dryas Boundary (YDB). Until now, evidence supporting this hypothesis has come only from terrestrial sediment and ice-core records. Here we report the first discovery of similar impact-related proxies in ocean sediments from four marine cores in Baffin Bay that span the YDB layer at water depths of 0.5–2.4 km, minimizing the potential for modern contamination. Using scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS) and laser ablation ICP-MS, we detect synchronous abundance peaks of metallic debris geochemically consistent with cometary dust, co-occurring with iron- and silica-rich microspherules (4–163 μm) that are predominantly of terrestrial origin with minor (<2 wt%) ET contributions. These microspherules were likely formed by low-altitude touchdown airbursts and surface impacts of comet fragments and were widely dispersed. In addition, single-particle ICP-TOF-MS analysis reveals nanoparticles (<1 μm) enriched in platinum, iridium, nickel, and cobalt. Similar platinum-group element anomalies at the YDB have been documented at dozens of sites worldwide, strongly suggesting an ET source. Collectively, these findings provide robust support for the YDIH. The impact event likely triggered massive meltwater flooding, iceberg calving, and a temporary shutdown of thermohaline circulation, contributing to abrupt Younger Dryas cooling. Our identification of a YDB impact layer in deep marine sediments underscores the potential of oceanic records to broaden our understanding of this catastrophic event and its climatological impacts.